1967
DOI: 10.1037/h0025143
|View full text |Cite
|
Sign up to set email alerts
|

Performance changes in escape conditioning following shifts in the magnitude of reinforcement.

Abstract: Reinforcement magnitude in a water-tank escape conditioning situation with rats (N = 64) was shifted from low to high and vice versa with appropriate controls after 60 training trials. Following the increase in reinforcement overall performance and the percentage of noncompeting response trials gradually increased to a level appropriate to the higher reinforcement magnitude with no contrast or "elation effect." With a decrease in reinforcement magnitude, on the other hand, the overall performance and the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

1968
1968
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 12 publications
1
21
1
Order By: Relevance
“…Reinforcement for the avoidance response, whether from termination of the CS or from the safety signal, therefore decreases markedly with consecutive avoidances. Both when a response is positively reinforced by appetitive stimuli (Crespi, 1942;Stebbins, 1962;Zeaman, 1949) and when it is reinforced by termination of an aversive stimulus (Strub, 1963;Woods, 1967), a decrease in reinforcement produces an increase in response latencies. In avoidance, however, one finds a decrease, not an increase, in response latencies throughout consecutive avoidances.…”
Section: Reinforcement Of the Avoidance Responsementioning
confidence: 99%
“…Reinforcement for the avoidance response, whether from termination of the CS or from the safety signal, therefore decreases markedly with consecutive avoidances. Both when a response is positively reinforced by appetitive stimuli (Crespi, 1942;Stebbins, 1962;Zeaman, 1949) and when it is reinforced by termination of an aversive stimulus (Strub, 1963;Woods, 1967), a decrease in reinforcement produces an increase in response latencies. In avoidance, however, one finds a decrease, not an increase, in response latencies throughout consecutive avoidances.…”
Section: Reinforcement Of the Avoidance Responsementioning
confidence: 99%
“…Although this is a familiar observation when an appetitive reinforcer is used, most studies of thermally motivated behavior have not reflected this property of thermal reinforcers. Woods and his colleagues (Woods, Davidson, & Pebus, 1964;Woods & Feldman, 1966;Woods & Holland, 1966;Woods, 1967) have shown that rats will swim faster for a larger reduction in water temperature but were unable to establish the continuum between satiety and incentive.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute overall speed scores were made relative to terminal acquisition and terminal extinction performance by the use of Anderson's (1963) shape-function method. The extinction analyses will focus on the overall speed measure rather than the midsection speeds, for previous reports have indicated the latter are a less sensitive measure of performance (e.g., Woods, 1967;Woods & Schutz,1965).…”
Section: Resultsmentioning
confidence: 99%